Is Coronavirus disease (COVID-19) case fatality ratio underestimated? - Abrar Ahmad Chughtai; Asim Ali Malik (University of New South Wales, 2020)
The number of cases of coronavirus disease (COVID-19) is increasing rapidly and case fatality ratio (CFR) is estimated to be around 2 to 3%. However, the epidemic is still ongoing and the outcome of many sick cases of COVID-19, particularly the outcome of severe cases, is not yet available, which may lead to underestimation of CFR. This was observed during the initial phase of severe acute respiratory syndrome coronavirus (SARS-CoV) outbreak as well, where CFR increased with the passage of time. We estimated the CFR of COVID-19 by extrapolating the data using SARS as an analogy. According to our estimates, the actual CFR of COVID-19 may be around 4.4 to 4.8%. However, these results should be interpreted with cautions as we did not adjust for many confounding factors. Various epidemiological and modelling techniques can be used to estimate CFR of COVID-19 during the epidemic. Precise estimates of CFR will be available after the end of the epidemic when the outcome of all cases will be available.